Disclosing Islamic values and cultures via museums in tourism industry - Ahmad Yunus Mohd Noor; Najwa Amalina Abdul Wahab (Penerbit Universiti Kebangsaan Malaysia, 2018)
Islamic values and cultures can be easily seen through its believers. It is due to the normal human behavior that will make an expectation when seeing somebody’s attitude spontaneously. In tourism industry, museums are the most important things to introduce or to expose local cultures and values especially in Melaka as a World Historical Heritage. Hence, this study aims to investigate how the museums in Central Melaka attempt to sustain Islamic values, to observe on how the museums approach in exposing Islamic values towards the tourist and to investigate the tourist awareness on museums activities during their visit. The study used a qualitative method which data is collected by interviewing Muslim and non-Muslim tourists as well as person in-charge of the museums. Five museums have been selected for this study due to the opportunities on exposing and introducing Islamic values to the tourist. The results show that museums do have the ability to show Islamic values and cultures. One of the informants express that Melaka has its own uniqueness which could not be found in any other places. This study has been done to gather sources as a preparation for research entitled ‘Influence of Tourism towards Sustainability of Islamic Values’.